Carbamazepine and Resistant Hypocalcemia - Kurt, Abdullah; Kurt, Ayşegül Neşe Çıtak; Aydın, Mustafa; Kabakuş, Nimet (Fırat University, 2007)
The patient, who was diagnosed epilepsy eight years ago, has been observed since then. The patient has been using carbamezapine for the last three years. He who did not have any seizures in the last year was clinically diagnosed status epilepticus. Status epilepticus was determined to have resulted from severe hypocalcemia. ©2007, Firat University, Medical Faculty

Kliniğimizde sekiz yıldır epilepsi tanısı ile izlenen hasta, son üç yıldır karbamazepin kullanıyordu ve son bir yıldır da hiç nöbeti yokken status epileptikus kliniği ile başvurdu. Status epileptikusun ağır hipokalsemiden kaynaklandığı belirlendi. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Karbamezapin ve Dirençli Hipokalsemi